IMPLEMENTASI PROGRAM BUDAYA SEKOLAH ISLAMI NURUSSHIBYAN(BISYA) DALAM PENINGKATAN AKHLAK KARIMAH SISWA DI SMP NURUSSHIBYAN PAGUYANGAN BREBES - Baeti Rahmawati (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT This research is qualitative descriptive research. It took Nurushibyan JHS, Paguyangan, Brebes with the teachers and learners as the subjects. The applied data collection techniques were observation, in-depth interview, and documentation. The validity test used data triangulation. The data analysis techniques consisted of data display and data conclusion. On the other hand, the implementation analysis of the Islamic School Program was done with AlGhazali's method of moral education. The findings showed that the school had an Islamic Culture Program (BISYA). The background of the program implementation was due to the degraded morals and Islamic knowledge of the learners. The school applied for the program by instilling Islamic values with Mujahadah, riyadhoh, exemplary, habituation, reward, and punishment methods. They became the most effective methods to succeed in the program. It was realized into two activity components. The first was the academic field, consisting of 1) reading and writing literacy, 2) realizing Islamic learning culture, and 3) upholding science and knowledge. The second one dealt with religious character education empowerment. It was grouped into 1) a 7-culture program (smile, greet, call, shake the hand, polite, and sympathetic), 2) morning habituation (dhuha prayer, saluting, and reciting AlQur’an), 4) Al-Qur’an literate (BabahQu), 5) full-day class for takhfidzul Qur'an, 6) doing good things, 7) dzikro majlis of Nurusshibyan for the learners’ parents, and 8) environmental awareness. BISYA program implementation was very important for the school to create khoirunnas an fa’uhum linnas generation. The program implication had positive impacts for the school, such as good morals of the learners, sosial trust seen from the learners’ input numbers, effective learning atmosphere, and sosial awareness Keywords: Islamic School Culture, Morals ABSTRAK Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Lokasi penelitian di SMP Nurusshibyan Paguyangan Brebes, dengan subjek penelitian yaitu guru dan siswa. Teknik pengumpulan data yang digunakan adalah observasi, wawancara mendalam dan dokumentasi. Uji keabsahan menggunakan triangulasi data. Teknik analisis data, penyajian data dan pengambilan simpulan. Hasil penelitian menunjukan SMP Nurusshibyan memilki Program Budaya Islami Nurusshibyan (BISYA), latar belakang penerapan program BISYA dikarenakan semakin menurunnya akhlak dan pengetahuan keislaman siswa. SMP Nurusshibyan Paguyangan, mengimplementasikan program Budaya Sekolah Islami Nuruushibyan (BISYA) melalui penanaman nilai-nilai islami yang dilakukan dengan metode Mujahadah, riyadhoh, keteladanan, pembiasaan serta metode ganjaran dan hukuman. Metode ini sangat efektif dalam keberhasilan pelaksanaan program BISYA yang diwujudkan dalam dua komponen kegiatan, pertama pada bidang akademik yakni program:1)literasi baca tulis, 2)mewujudkan budaya belajar islami dan 3)penghargaan terhadap ilmu pengetahuan. Kedua, bidang penguatan pendidikan karakter religiusitas yakni program ; 1)Budaya 7S (Senyum,salam,sapa, salim sopan, santun, simpatik),2) pembiasaan pagi (sholat duha,sholawatan dan membaca Al quran), 3) sholat dhuhur bagi dan sholat ashar berjama’ah bagi siswa kelas fullday dan ekdtrakurikuer, 4)bebas buta huruf al-Qur’an (BabahQu), 5)kelas fullday takhfidzul Qur’an, 6) tabaratku (tabungan akhiratku), 7)majlis dzikro Nurusshibyan bagi orang tua/wali siswa dan 8) peduli lingkungan. Implementasi program BISYA ini menjadi sangat penting bagi sekolah dalam upayanya untuk melahirkan generasi khoirunnas an fa’uhum linnas. Kata Kunci: Budaya sekolah Islami, Akhlak karimah.